Responsive cell–material interfaces - Dhowre, Hala S.; Rajput, Sunil; Russell, Noah A.; Zelzer, Mischa (Futuremedicine, 2015)
Major design aspects for novel biomaterials are driven by the desire to mimic more varied and complex properties of a natural cellular environment with man-made materials. The development of stimulus responsive materials makes considerable contributions to the effort to incorporate dynamic and reversible elements into a biomaterial. This is particularly challenging for cell–material interactions that occur at an interface (biointerfaces); however, the design of responsive biointerfaces also presents opportunities in a variety of applications in biomedical research and regenerative medicine. This review will identify the requirements imposed on a responsive biointerface and use recent examples to demonstrate how some of these requirements have been met. Finally, the next steps in the development of more complex biomaterial interfaces, including multiple stimuli-responsive surfaces, surfaces of 3D objects and interactive biointerfaces will be discussed.